Percutaneous Image-Guided Drainage of Abdominal Fluid Collections in Children: Technical Considerations and Clinical Scenarios - Gallo-Bernal, Sebastian; Cahalane, Alexis M.; Gee, Michael S. (Digestive Disease Interventions, 2022)
While initially conceived and designed for adults, percutaneous image-guided drainage of abdominal pelvic and fluid collections has revolutionized the management of several pediatric pathologies. Interventional radiology procedures markedly reduce morbidity and mortality by offering a definitive minimally invasive approach or allowing a cleaner and less challenging subsequent open approach. These procedures are associated with improved patient comfort and rapid recovery. While similar techniques apply to children and adults, successful adaptation of image-guided interventional techniques in children requires consideration of several critical differences. This review aims to discuss the indications, contraindications, and technical aspects of percutaneous image-guided drainage of abdominal and pelvic fluid collections in children.
Keywords: pediatric; fluid collections; drainage